Promoting transdisciplinary learning through a summer course on climate, water, and agriculture. Issue 1 (4th August 2020) - Lekies, Kristi S.; Moore, Richard H.
Abstract: Transdisciplinary approaches increasingly are needed to address complex environmental problems. Students can benefit from research and learning opportunities in which they investigate issues, integrate knowledge across disciplines, engage with stakeholders, collaborate with others, and devise solutions. This paper presents information on a 1‐week intensive transdisciplinary course focused on climate, water, and agriculture for undergraduate and graduate students. The course, which was held at The Ohio State University's Stone Laboratory on Lake Erie, was offered over 3 years and utilized the local and regional context for investigation and inquiry. Presentations, discussions, experiential and field activities, and guest presentations were used as a way to promote student learning. Students felt positive about their participation and rated the transdisciplinary aspects of the course highly. Ideas from this course can be used to develop similar courses and learning experiences in other settings and on other environmental topics. Instructors are encouraged to utilize campus and local resources, recruit students from a diversity of disciplines, and align content and activities to build transdisciplinary skills.